Evaluation of Relationships between Growth Rate, Tree Size, Lignocellulose Composition, and Enzymatic Saccharification in Interspecific Corymbia Hybrids and Parental Taxa - Healey, Adam L.; Lee, David J.; Lupoi, Jason S.; Papa, Gabriella; Guenther, Joel M.; Corno, Luca; Adani, Fabrizio; Singh, Seema; Simmons, Blake A.; Henry, Robert J. (Frontiers in Plant Science, 2016)
In order for a lignocellulosic bioenergy feedstock to be considered sustainable, it must possess a high rate of growth to supply biomass for conversion. Despite the desirability of a fast growth rate for industrial application, it is unclear what effect growth rate has on biomass composition or saccharification. We characterized Klason lignin, glucan, and xylan content with response to growth in Corymbia interspecific F1 hybrid families (HF) and parental species C. torelliana (CT) and C. citriodora subspecies variegata (CCV) and measured the effects on enzymatic hydrolysis from hydrothermally pretreated biomass. Analysis of biomass composition within Corymbia populations found similar amounts of Klason lignin content (19.7-21.3%) among parental and hybrid populations, whereas glucan content was clearly distinguished within CCV (52%) and HF148 (60%) as compared to other populations (28-38%). Multiple linear regression indicates that biomass composition is significantly impacted by tree size measured at the same age, with Klason lignin content increasing with diameter breast height (DBH) (+0.12% per cm DBH increase), and glucan and xylan typically decreasing per DBH cm increase (-0.7% and -0.3%, respectively). Polysaccharide content within CCV and HF-148 were not significantly affected by tree size. High-throughput enzymatic saccharification of hydrothermally pretreated biomass found significant differences among Corymbia populations for total glucose production from biomass, with parental CT and hybrids HF-148 and HF-51 generating the highest amounts of glucose (~180 mg/g biomass, respectively), with HF-51 undergoing the most efficient glucan-to-glucose conversion (74%). Based on growth rate, biomass composition, and further optimization of enzymatic saccharification yield, high production Corymbia hybrid trees are potentially suitable for fast-rotation bioenergy or biomaterial production.